2022
DOI: 10.1017/s2045796022000518
|View full text |Cite
|
Sign up to set email alerts
|

Long-term psychological profile of general population following COVID-19 outbreak: symptom trajectories and evolution of psychopathological network

Abstract: Aims COVID-19 has long-term impacts on public mental health, while few research studies incorporate multidimensional methods to thoroughly characterise the psychological profile of general population and little detailed guidance exists for mental health management during the pandemic. This research aims to capture long-term psychological profile of general population following COVID-19 by integrating trajectory modelling approaches, latent trajectory pattern identification and network analyses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Secondly, the sample was collected via online may limit its representativeness of the Chinese population. However, this large sample size study recruited participants from 32 provinces in China, which enhances the generalizability of our findings; the demographic characteristics (such as age, sex ratio, education level, and employment status) [ 47 , 48 ] and daily social media use [ 49 ] were similar to those of other large-scale representative studies in China. Moreover, the prevalence of PSMU in our sample was consistent with other epidemiological studies during the pandemic, indicating reasonable representativeness of our sample [ 50 ].…”
Section: Discussionmentioning
confidence: 78%
“…Secondly, the sample was collected via online may limit its representativeness of the Chinese population. However, this large sample size study recruited participants from 32 provinces in China, which enhances the generalizability of our findings; the demographic characteristics (such as age, sex ratio, education level, and employment status) [ 47 , 48 ] and daily social media use [ 49 ] were similar to those of other large-scale representative studies in China. Moreover, the prevalence of PSMU in our sample was consistent with other epidemiological studies during the pandemic, indicating reasonable representativeness of our sample [ 50 ].…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, a prediction model used in a Korean study found that the actual number of patients with schizophrenia receiving outpatient treatment decreased by 1,605 compared to the expected number during the early COVID-19 outbreak ( 21 ). Although, there was no evidence from anywhere that the prevalence of SMI increased during the epidemic, the decreased number of SMI-related outpatient visits due to COVID-19 likely represents a large number of SMI patients that were not able to receive continuous treatment, rather than a decrease in the prevalence of SMI, given the evidence that most countries have reported increased rates of mental illness due to the pandemic ( 22 , 23 ). Untreated SMI can result in an increase in the severity of symptoms and relapse of disease, and may even lead to social and financial problems or suicide and criminal behavior ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Each item is scored from 0 (“none”/“very satisfied”) to 4 (“very severe”/“very dissatisfied”), with a total score from 0 to 28. The psychometric properties of the ISI Chinese version have been validated in Chinese populations ( 57 , 58 ). Higher scores indicated more severe insomnia.…”
Section: Methodsmentioning
confidence: 99%